2021
DOI: 10.3390/forecast3020026
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Operational Application of a WRF-Hydro-Based Fluvial Flood Forecasting System in the Southeast Mediterranean

Abstract: The Southeast Mediterranean (SEM) is characterized by increased vulnerability to river/stream flooding. However, impact-oriented, operational fluvial flood forecasting is far away from maturity in the region. The current paper presents the first attempt at introducing an operational impact-based warning system in the area, which is founded on the coupling of a state-of-the-art numerical weather prediction model with an advanced spatially-explicit hydrological model. The system’s modeling methodology and foreca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In addition, more than thirty-two flood events have affected the area between 2004 and 2014, with eighteen of these characterized as significant flood episodes based on the hydrological response intensity of the study catchment. The application of a system based on the coupling between the Weather Research and Forecasting (WRF) numerical weather prediction model and its hydrological extension package (WRF-Hydro) by Giannaros et al [48] showed that the majority of the flash flood events in Megalo Rema catchment took place during the wet period of the hydrological year and were associated with typical, for the study area, wet-season cyclonic activity [49]. This is due to the global atmospheric circulation during the autumn and winter, which interacts with the complex geomorphology and land-sea temperature contrast in the Eastern Mediterranean region, favoring the development of cyclonic atmospheric conditions [50].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, more than thirty-two flood events have affected the area between 2004 and 2014, with eighteen of these characterized as significant flood episodes based on the hydrological response intensity of the study catchment. The application of a system based on the coupling between the Weather Research and Forecasting (WRF) numerical weather prediction model and its hydrological extension package (WRF-Hydro) by Giannaros et al [48] showed that the majority of the flash flood events in Megalo Rema catchment took place during the wet period of the hydrological year and were associated with typical, for the study area, wet-season cyclonic activity [49]. This is due to the global atmospheric circulation during the autumn and winter, which interacts with the complex geomorphology and land-sea temperature contrast in the Eastern Mediterranean region, favoring the development of cyclonic atmospheric conditions [50].…”
Section: Study Areamentioning
confidence: 99%
“…Very low to moderate prone areas appear mainly at forests and areas covered by natural vegetation (see Table 8). The analysis performed by Giannaros et al [48] in an attempt to introduce an operational impact-based warning system in the area, coupling a state-of-the-art numerical weather prediction model with an advanced, spatially explicit hydrological model, provided some preliminary discharge thresholds in terms of flash flooding's socioeconomic impacts. Minimal impact was reported when the peak discharge in the mouth of Megalo Rema was lower than 20 m 3 /s, whereas maximum stream discharges that ranged from 20 m 3 /s to 40 m 3 /s were associated with major impact.…”
Section: Hbasicmentioning
confidence: 99%
See 1 more Smart Citation
“…These tools include the WRF model and the integrated multi‐satellite retrievals for global precipitation measurement (GPM‐IMERG) algorithm. The WRF model is used by the CyFFORS pilot flood forecasting service and the National Observatory of Athens (NOA) for operational weather forecasting (Giannaros et al, 2021; Giannaros, Kotroni, Lagouvardos, Giannaros, & Pikridas, 2020), while the GPM‐IMERG algorithm is used by NOA for tracking storms' evolution in near real time. The performance of both tools in estimating rainfall is evaluated against ground‐based observations.…”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that no preventative measures or defense structures can be completely effective, flood-risk management systems should provide as much sufficient lead time as feasible. Therefore, the implementation and operation of flood forecasting and warning systems are important parts of flood management services [3][4][5].…”
Section: Introductionmentioning
confidence: 99%